A family‐centered approach to dementia caregiving: The case of Arab Americans: Dementia care research (research projects; nonpharmacological)/Cross‐cultural studies and cultural/linguistic adaptations. (7th December 2020) - Ajrouch, Kristine J; Janevic, Mary; Antonucci, Toni C
Abstract: Background: Research findings increasingly show that the primary caregiver paradigm is not a good fit for many cultures (Gallagher‐Thompson et al., 2000; Dilworth‐Anderson et al., 1999; Aranda & Knight, 1997). In terms of Arab American communities, findings show the need for a family‐centric approach to caring for older adults (Ajrouch, 2017; Ajrouch & Fakhoury, 2013; Sengstock, 1996). The Arab population in Michigan grew 47% between 2000 and 2013, estimated at over 300, 000 residents (Arab American Foundation Institute, 2014), and 11% are aged 65+ (American Community Survey, 2013‐2018). We advance a family systems framework by invoking convoys of caregiving (Sherman, Webster & Antonucci, 2013), highlighting that all caregivers, but especially in certain cultures, are surrounded by key others. This paper presents the process by which we developed a culturally congruent Alzheimer's Disease (AD) caregiver intervention for Arab American families. Method: Three focus groups were organized with Arab Americans caring for a family member with AD. One focus group was organized with professionals who work with Arab Americans. Focus group discussions were held at a local Arab American social service organization, and gathered data on the role of family in caregiving, Arab American needs, and reactions to proposed intervention formats. Inductive analysis identified and refined study themes applied to modify an existing support program from the Alzheimer's Association. Result: Results identified universal (e.g., burnout, ) as well as culturally unique themes around the family caregiving experience. Culturally unique themes included "national origins, " which alerts us to ensure examples and scenarios used are familiar, but also introduces need for ensuring and communicating confidentiality; "family dynamics, " which introduces need to build on strengths, while at same time convey importance of accepting help; and "cultural ideals, " which shape how to introduce formal support options. We illustrate how results were applied to modify program delivery and content. Conclusion: This approach provides direction for addressing cultural needs/preferences within family contexts. Successful modification of an existing intervention includes capturing group ideals, engaging with community partners as equals, and making cultural representations visible. Next steps will involve evaluation of the modified program, program refinement and a final tool kit.